Take vedolizumab home: transition from intravenous to subcutaneous treatment - Kaituo Huang; Lingya Yao; Jing Liu; Qian Cao (SAGE Publishing, 2024)
In 2020, the European Medicines Agency approved subcutaneous (SC) vedolizumab (VDZ) for the maintenance treatment of adult patients with moderate to severe inflammatory bowel disease (IBD). This article reviews the efficacy, safety, persistence, pharmacology, patient satisfaction, and economic implications of transitioning to SC VDZ treatment and explores whether SC formulations can be recommended by the same guidelines as intravenous (IV) formulations. Clinical trials and real-world evidence indicate that transitioning from IV to SC VDZ in patients with IBD maintains clinical, biochemical, and patient-reported clinical remission and is well-tolerated, with no new safety issues identified, except for injection site reactions. Moreover, SC VDZ has an exposure-response relationship and low immunogenicity, is economical, and provides a high level of patient satisfaction. Owing to these advantages, transitioning may be advisable. In the future, more studies are needed to clarify the exact role of SC VDZ in IBD treatment, including optimization and transitioning strategies and individualized treatments based on baseline characteristics.